Mechanical property analysis of stainless steel bolt. Issue 2 (April 2021) - Ren, Facai; Tang, Xiaoying; Si, Jun; Xu, Jinsha
Abstract: Tensile property test, hardness test, chemical composition test, metallographic analysis and solution treatment analysis were carried out for stainless steel bolt. The results show that the Cr content is slightly lower than the requirements of relevant standards, and the tensile properties and hardness meet the requirements. Comparing the microstructure of the original sample with that of the sample after solution treatment, it can be seen that there are a lot of acicular martensite phase in the original sample, and there are a lot of carbide precipitation at the grain boundary, but no carbide precipitation is found at the grain boundary of the sample after solution treatment.